A Very Rare Case: HPV-Negative Vulvar Cancer in an Adolescent. (1st February 2018) - Kahramanoglu, Ilker; Turan, Hasan; Oner, Yahya Ozgun; Bese, Tugan; Ilvan, Sennur; Arvas, Macit; Demirkiran, Fuat
Abstract : Carcinoma of the vulva is usually regarded as a disease of older women, with the typical age of 65–85 years. There are a limited number of reports of vulvar cancer cases younger than 30 years. These patients have usually risk factors such as human papillomavirus (HPV) infection and immunosuppression. Herein, we present a case of invasive squamous vulvar cancer in an 18-year-old patient without any risk factor. Vulvar radical local excision and bilateral inguinal sentinel lymph node biopsies were performed. The clitoris was preserved during the surgery. Patient did not receive adjuvant therapy. Follow-up after 12 months of the disease showed no evidence of disease. Vulvar carcinoma in very young women may develop without any predisposing factor. Early detection will result in better survival. So, there should be a high index of suspicion when a vulvar lesion is seen, even if the patient falls below the typical age range and does not carry any well-known risk factors such as HPV infection and immunodeficiency.